Assessment Of Neuropsychological And Behavioral functions With Yoga Intervention In Early Adolescent Obesity - Joshi, Ruchira R; Rathi, Sunanda S (International Research Journal of Ayurveda & Yoga, 2024)
Background: -Adolescent Obesity is causing serious public health concern and in many countries threatening the viability of basic health care delivery. Apart from physical problems there are issues which affect neuropsychological and behavioral well-being of the obese child. Yoga is found to have effective solutions forneuropsychological and behavioral problems in adolescent obesity if practiced in early age. Aim:-To asses effect of Yoga intervention on neuropsychological and behavioral assessments in early adolescent Obesity. Method :-Randomized Controlled Trial ( Yoga n = 30 and Control n = 30 ) was conducted on 60 obese early adolescents with average age of 11.32 yrs ( ± 1.43 ) and average weight of 61.43 Kg( ± 10.42 ) for 40 days. Neuropsychological and behavioral parameters like Body Awareness Questionnaire( BAQ ) , Rosenberg Self-esteem Scale ( RSES ) and Child Eating Behavior Questionnaire ( CEBQ ) , Six Letter Cancellation Test ( SLCT )and Digit Letter Substitution test ( DLST ) were assessed before and after intervention for both the groups. Results :-Significant results were observed in improvement of self-esteem, neuropsychological functions and eating behavior with Yoga group. SLCT of Yoga group improved better as compare to Control group. Yoga group showed better performance than Control group in other parameters but without significance. Conclusion :-Yoga intervention is witnessed to have affirmative impact on neuropsychological and behavioral functions in early adolescent obesity.